Worse quality of life in young and recently diagnosed breast cancer survivors compared with female survivors of other cancers: A cross‐sectional study. Issue 11 (16th August 2016) - Li, Jingmei; Humphreys, Keith; Eriksson, Mikael; Dar, Huma; Brandberg, Yvonne; Hall, Per; Czene, Kamila
Abstract : Literature focusing on health‐related quality of life (HRQoL) by cancer site among women only is scarce. This study examines HRQoL of breast cancer (BC) survivors compared with female survivors of other cancers, and to understand which subgroups of BC survivors were particularly at risk of reduced HRQoL. We placed emphasis on young (<50 years) and recently diagnosed (≤5 years) survivors, where the deficits in HRQoL were most pronounced. The cross‐sectional study consisted of 2, 224 BC survivors, 8, 504 non‐cancer controls and 2, 205 other cancer survivors in the Karma study. We examined HRQoL differences using linear regression analyses in the whole cohort and in a subset of young and recently diagnosed BC survivors ( n = 242) and female survivors of other cancers ( n = 140) with comparable ages at diagnosis (43.6 vs 43.6, p = 0.917) and time since diagnosis (2.3 vs 2.8 years, p < 0.001). HRQoL was assessed using the EORTC QLQ‐C30 questionnaire. While only cognitive functioning was significantly compromised in BC survivors compared with survivors of other cancers when women of all ages were included, young BC survivors reported significantly lower HRQoL on multiple functional scales (global quality of life, emotional, role, social and cognitive functioning) and experienced more fatigue and insomnia. BC survivors with any prior medical history of mental disorders reported poorer HRQoL than those without such a history. We also observed a close–knit relationship between tumor and treatment characteristics. BC survivors perform poorly in HRQoL in comparison with female survivors of other cancers. Our results emphasize the importance of age‐ and gender‐appropriate comparison groups. Abstract : What's new? Women who survive breast cancer may live many years beyond the time of their original diagnosis. Little is known, however, about their health‐related quality of life (HRQoL) in the years after treatment. In this cross‐sectional study, HRQoL among breast cancer survivors was found to be comparable with that of age‐matched controls in the general population. Nonetheless, young breast cancer survivors fared disproportionately worse in many aspects of HRQoL when compared with female survivors of other cancers, suggesting that young breast cancer survivors may benefit from being more prepared for the physical and mental impacts of their disease.